2013
DOI: 10.1088/0004-637x/770/2/143
|View full text |Cite
|
Sign up to set email alerts
|

WIDE INTEGRAL-FIELD INFRARED SPECTROSCOPY OF THE BRIGHT [Fe II] SHELL IN THE YOUNG SUPERNOVA REMNANT G11.2–0.3

Abstract: We present the results of wide integral-field near-infrared (1.0-1.8 µm) spectroscopic observations of the southeastern shell of the young core-collapse supernova remnant (SNR) G11.2−0.3. We first construct [Fe II] 1.644 µm line images of three bright clumps from the obtained spectral image cubes and compare them with those of other transitions such as [Fe II] 1.257, [Fe II] 1.534 and He I 1.083 µm line images. This allows us to estimate the electron density (∼ 4,700-9,400 cm −3 ) and extinction (A V ∼ 16-20 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Along with this front shock expanding into the surrounding medium, there exists a reverse shock which propagates back into SN material. Strong NIR [Fe II] lines are emitted when these shocks interact with dense material, which could be either the SN or the circumstellar material for young SNRs, and usually interstellar material for middle-aged SNRs (e.g., Oliva et al 1989Oliva et al , 1990Koo et al 2007;Lee et al 2009;Moon et al 2009;Lee et al 2013, see also Koo 2013 and references therein). Moreover, Fe, being the end product of the stellar nucleosynthesis process, forms a main component of the supernova ejecta; the materials ejected from the deep layers of the progenitor are often enriched in Fe.…”
Section: Supernova Remnantsmentioning
confidence: 99%
“…Along with this front shock expanding into the surrounding medium, there exists a reverse shock which propagates back into SN material. Strong NIR [Fe II] lines are emitted when these shocks interact with dense material, which could be either the SN or the circumstellar material for young SNRs, and usually interstellar material for middle-aged SNRs (e.g., Oliva et al 1989Oliva et al , 1990Koo et al 2007;Lee et al 2009;Moon et al 2009;Lee et al 2013, see also Koo 2013 and references therein). Moreover, Fe, being the end product of the stellar nucleosynthesis process, forms a main component of the supernova ejecta; the materials ejected from the deep layers of the progenitor are often enriched in Fe.…”
Section: Supernova Remnantsmentioning
confidence: 99%
“…• n e ∼ a few thousand cm −3 for T e ∼ 5000 K in case of a dense supernovae filament (see e.g. Lee et al 2013);…”
Section: Physical Constraints On the Surrounding Mediummentioning
confidence: 99%
“…More recently, it was found that the NIR spectra of young SNRs are interesting, sometimes showing many ionic lines from supernova (SN) ejecta material (Gerardy & Fesen, 2001;Koo et al, 2007;Moon et al, 2009;Lee et al, 2013;Koo et al, 2013). In the Milky Way, there are about 300 SNRs, and 20-30 of them are younger than several thousand years.…”
Section: Introductionmentioning
confidence: 99%